Corporate Governance in Nepal - Pokhrel, Dilli Ram (Socio-Economic Development Panorama, 2008)
For the last few years, the corporate governance has been a matter of growing academic interest in the policy studies. Given the infant stage of securities market development and gradual transformation of the external sources of corporate finance from bank to market, Nepal is passing through a transitional phase of institutional and governance reform. The high concentration of corporate ownership structure and dominance of family business groups in corporate affairs have become major constraints in exercising good corporate governance. Nevertheless, a number of governance reforms are underway and some positive symptoms have been observed in the banks and financial institutions. To ensure a good corporate governance in Nepal requires a joint effort of the investors (promoters) who need to be more transparent, responsible and socially accountable; the shareholders who must actively participate in their corporate affairs to help prevent any fraudulent and insider practices and; the regulatory authority that should effectively enforce rules and regulations in order to protect the rights of all stakeholders and create favorable environment to enhance good corporate governance culture. This article presents an introductory overview of the policy framework, enforcement mechanism, compliance practices and main features of corporate governance in Nepal. Socio-Economic Development Panorama Vol.1(1) 2007 pp.39-53